On Power and Ideology : The Managua lectures - Chomsky, Noam (London Pluto Press, 2015)
Chomsky's combative lectures from Nicaragua during the Cold War period, given at the height of his intellectual prowess.
Keywords: United States -- Diplomatic relations -- National security